2018
DOI: 10.1016/j.ijsu.2018.02.061
|View full text |Cite
|
Sign up to set email alerts
|

Preventable risk factors of mortality after hip fracture surgery: Systematic review and meta-analysis

Abstract: This meta-analysis explicitly indicated that malignancy, nursing home residence, time to surgery (>2days/<2days), pulmonary disease, diabetes, and cardiovascular disease significantly increased the risk of mortality after hip fracture surgery. These preventable risk factors may be used to create algorithms that are more effective and pertinent to reduce the mortality following hip fracture surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 37 publications
4
76
2
1
Order By: Relevance
“…This score enables a standardized risk assessment score for intra operative and post-operative risk 26,27 . A meta-analysis of Chang et al conducted in 2018, including 25,349 patients from16 studies (13 prospective and 3 retrospective), found a significant association between mortality after HF and several risk factors including cardiac disease, diabetes and cancer 14 . Charleston Comorbidity Index (CCI) was described as able to predict postoperative complications after HF surgery however the odds ratios were not very large 28 .…”
Section: Discussionmentioning
confidence: 99%
“…This score enables a standardized risk assessment score for intra operative and post-operative risk 26,27 . A meta-analysis of Chang et al conducted in 2018, including 25,349 patients from16 studies (13 prospective and 3 retrospective), found a significant association between mortality after HF and several risk factors including cardiac disease, diabetes and cancer 14 . Charleston Comorbidity Index (CCI) was described as able to predict postoperative complications after HF surgery however the odds ratios were not very large 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies that evaluated treatment outcomes including those for patients who received conservative treatment, the annual mortality rate ranged from 10% to 40% [10][11][12]. Factors reportedly associated with higher mortality included aging, male sex, cognitive dysfunction, cardiovascular disease, respiratory disease, diabetes mellitus, and malignant tumors [10][11][12][13][14][15]. The Charlson comorbidity index [12] and the American Society of Anesthesiologists Physical Status Classification System [13] are were also both reportedly associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…About the timing of surgery, the National Institute for Health and Care Excellence recommends early surgery within 48 hours [4]; this strategy is associated with advantages such as reduced complications and improved functional recovery. Although early surgery is reported to be positively associated with the life prognosis [14], it is generally possible that a patient with no or few complications has undergone early surgery, and the effect of bias may be considered. In a Japanese study, 2010-2014 data showed that only 22.5% of patients underwent surgery within 2 days of hospitalization, and the risk of pneumonia and pressure ulcers was significantly reduced in the early surgery group [19].…”
Section: Discussionmentioning
confidence: 99%
“…BMI closest to date of surgery, within 1 year, was used for analysis. Diabetes mellitus was selected as an explanatory variable because of known associations with mortality in the setting of hip fractures (Chang et al, 2018; Meng et al, 2019) and altered analgesic requirements (Weiner et al, 2019). Smoking status was selected as an explanatory variable cause of known associations with complications in the setting of hip fractures (Ray, Aitken, McQueen, Court‐Brown, & Ralston, 2015) and altered analgesic requirements (Flanagan, Wysong, Ramey, & Vallier, 2018; Kuwabara et al, 2014; Walters, Cleck, Kuo, & Blendy, 2005).…”
Section: Methodsmentioning
confidence: 99%